2022
DOI: 10.3390/insects13060534
|View full text |Cite
|
Sign up to set email alerts
|

Diverse Host Plants of the First Instars of the Invasive Lycorma delicatula: Insights from eDNA Metabarcoding

Abstract: Identification of host plants of the invasive spotted lanternfly, Lycorma delicatula (Hemiptera: Fulgoridae), has been the focus of many studies. While the adults and late nymphs are relatively easy to observe on plants and to use for molecular gut-content analysis, studying the early instars is more challenging. This study is the continuation of our ongoing efforts to determine the host range for each developmental stage of L. delicatula. In the present study, we focused exclusively on the first nymphal insta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Without tree of heaven, SLF can develop to adulthood on select diets comprised of a single host plant species, though overall fitness is greater when multiple plant species are available (9)(10)(11) including tree of heaven (11,12). Molecular gut content analyses show SLF feed on a variety of species throughout their development (13)(14)(15). Together, these results suggest SLF visit multiple hosts to optimize their development and gather necessary nutrients that may be absent from their preferred host, tree of heaven, or that they require multiple plant species to attain adequate nutrition for survival and development (9).…”
Section: Introductionmentioning
confidence: 99%
“…Without tree of heaven, SLF can develop to adulthood on select diets comprised of a single host plant species, though overall fitness is greater when multiple plant species are available (9)(10)(11) including tree of heaven (11,12). Molecular gut content analyses show SLF feed on a variety of species throughout their development (13)(14)(15). Together, these results suggest SLF visit multiple hosts to optimize their development and gather necessary nutrients that may be absent from their preferred host, tree of heaven, or that they require multiple plant species to attain adequate nutrition for survival and development (9).…”
Section: Introductionmentioning
confidence: 99%
“…It is well established that earlier lifestages have a broad host plant range, which narrows with development (Kim et al 2011, Avanesyan and Lamp 2020, McPherson et al 2022); A. altissima is consistently a preferred host throughout their development (Dechaine et al 2021, Nixon et al 2022b) which makes this species ideal for trap deployment. Although fourth instar nymphs and adults are reported in higher numbers on A. altissima , these later lifestages have been reported consistently on a wide range of observed hosts such as Acer spp., J. nigra , and C. occidentalis L. (Rosales: Cannabaceae) (Dechaine et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Ailanthus altissima remained an acceptable host of L. delicatula throughout all lifestages in the field, although different lifestages can exploit available secondary hosts for discrete periods of time. Gut content analyses have shown that nymphal L. delicatula will frequently feed on a variety of plants (Avanesyan and Lamp 2020, McPherson et al 2022), and dispersing adults utilize alternate hosts such as Acer and Prunus spp. (Hepler et al, submitted).…”
Section: Discussionmentioning
confidence: 99%